Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1902/jop.2016.150504
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Wound Healing by Transplantation of Jaw Bone Marrow‐Derived Mesenchymal Stem Cells in Chitosan/Anorganic Bovine Bone Carrier Into One‐Wall Infrabony Defects in Beagles

Abstract: The combination of hJBMMSCs and C/ABB scaffolds could promote periodontal repair. Future studies are expected to further optimize the combination and lead to an ideal periodontal regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…The referred experiment used acute periodontal defects, which have a significantly greater capacity to self‐regenerate as compared to chronic supracrestal defects utilized in this study. In another experimental study, using bone marrow mesenchymal stem cells (BMMSCs) seeded on chitosan/anorganic bovine bone for treating acute surgically created one‐wall critical size infrabony periodontal reported a regeneration of 38% of total defect (Zang et al., ). The amount of periodontal regeneration achieved within the furcation (2.35 mm and 1.93 mm in control and test groups, respectively) can also be comparable with other experimental studies evaluating guided tissue regeneration with barrier membranes of expanded polytetrafluoethylene (e‐PTFE) (Lindhe et al., ; Polimeri et al., ) or with a combination of enamel matrix proteins and a bioabsorbable membrane (Donos, Sculean, Glavind, Reich, & Karring, ).…”
Section: Discussionmentioning
confidence: 99%
“…The referred experiment used acute periodontal defects, which have a significantly greater capacity to self‐regenerate as compared to chronic supracrestal defects utilized in this study. In another experimental study, using bone marrow mesenchymal stem cells (BMMSCs) seeded on chitosan/anorganic bovine bone for treating acute surgically created one‐wall critical size infrabony periodontal reported a regeneration of 38% of total defect (Zang et al., ). The amount of periodontal regeneration achieved within the furcation (2.35 mm and 1.93 mm in control and test groups, respectively) can also be comparable with other experimental studies evaluating guided tissue regeneration with barrier membranes of expanded polytetrafluoethylene (e‐PTFE) (Lindhe et al., ; Polimeri et al., ) or with a combination of enamel matrix proteins and a bioabsorbable membrane (Donos, Sculean, Glavind, Reich, & Karring, ).…”
Section: Discussionmentioning
confidence: 99%
“…Masson's trichrome staining performed by Sukpaita et al [33] found an increased amount of collagen and bone matrix in CS/Dicarboxylic acid scaffold with and without PDLCs seeding. In the study by Zang et al [38], the same test showed more dense and well-organized PDLCs in the chitosan scaffold with hJBMMSCSs than the chitosan/anorganic bovine bone and pure chitosan groups. ARS staining of hPDLCs performed by Xue et al [36] recorded more mineralized nodules on the nPLGA/nCS/nAG complex than in negative control group, showing the that this type of membrane may promote cell mineralization.…”
Section: Results Of Individual Studiesmentioning
confidence: 81%
“…ALP activity of periodontal ligament cells [21], osteoblasts [34,35], and mesenchymal stem or stromal cells [24] was assessed in four studies (Table 5). Three items analyzed the mineralization level of the newly formed bone with the Masson's trichrome staining method [27,33,38], two assessed it with the ARS staining [31,36] and one with the immunofluorescent staining technique for osteocalcin (OCN) [39] ( Table 6). Twelve of the selected papers performed their experiment in vivo, creating bone defects, which were later covered by CS-based scaffolds: Ge et al [21] created bilateral parietal bone defects (with a diameter of 5 mm) in eighteen eight-week-old rats (weight = 180-220 g), scoring the anesthetized cranial skin, exposing calvaria; parietal cranial 15 mm oval-shaped defects were obtained by Jayash et al [25] using a bone trephine drill.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…BMSC were used in 3 studies [58] [59], one of which was a one walled intra bony defect [60], PDLSC in 2 studies [61] [62], DPSC in 1 study [49] and adipose derived stem cell in one study [63] successfully. PDLSC were also used to treat periodontal fenestration defects and was able to form bone, PDL and cementum successfully [64].…”
Section: Furcation Defectsmentioning
confidence: 99%